The kissing tree : [large type] four novellas rooted in timeless love - Witemeyer, Karen; Jennings, Regina (Regina Lea); Dykes, Amanda; Deese, Nicole (Thorndike Press large print Christian romance series., 2021)
"A Texas-sized romance novella collection with stories spanning from 1868 to the present day. In Regina Jenning's Broken limbs, mended hearts, a small-town teacher has her credentials questioned by a traveling salesman. In Karen Witemeyer's Inn for a surprise, two opinionated collaborators must turn a doomed business venture into a successful romantic retreat. From roots to sky by Amanda Dykes follows a young WWII naval airman who heads to Texas to meet the sister of a lost compatriot. Heartwood by Nicole Deese is a modern-day romance about the groundskeeper of a historic inn who's reunited with someone from her past"--Back cover.